GEOSPATIAL DISTRIBUTIONS OF MALARIA AND ITS VULNERABILITY IN MINJIBIR, KANO STATE - Ibrahim Sufiyan; Muhammad K.D; Magaji J.I. (Acta Scientifica Malaysia, 2021)
Malaria is considered to be a deadly disease spread in almost all parts of Nigeria, especially in the Northern parts. This has to do with the climatic influence of the north-easterlies and the hot dry savannah couple with the attitude of health sanitation. This study captured the vulnerable areas where the malaria cases are severe and predominant using satellite images and data. The frequency of malaria prevalence was done on a daily, monthly and annual basis for the period of 3 years from 2017-2019. The outcome shows that people in Minjibir and 5 villages were sampled having high malaria prevalence in 2017 with 41.28%, 2018 has 35.19% and 2019 has 23.53%. The result indicates that malaria cases are dropping with a decrease from 2017 to 2019 by 17.75%.